2018
DOI: 10.1038/s41598-018-32767-7
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Pro-Uroguanylin Levels In Children And Their Relation To Obesity, Sex And Puberty

Abstract: Uroguanylin is a 16 amino acid peptide that constitutes a key component of the gut- brain axis with special relevance in body weight regulation. In childhood and adolescence, periods of life with notable metabolic changes; limited data exist, with measurements of pro-uroguanylin in adolescence but not in prepubertal children. This study investigates pro-uroguanylin circulating levels in children with obesity and its relationship with obesity, sex and pubertal development. We analyzed circulating prouroguanylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Although there is no direct evidence in the literature regarding the effects of linaclotide on energy homeostasis, recent reports have indicated that the activation of its receptor Gucy2c is involved in the control of food intake [3] and EE [7] in rodents. Moreover, in humans circulating levels of proUGN are altered in obese adult subjects [8] and children [20]. The fact that oral linaclotide acts through the central nervous systems targeting BAT thermogenesis and EE without affecting feeding behavior is similar to our previous findings in which a central infusion of UGN was able to induce the same effects [7].…”
Section: Discussionsupporting
confidence: 86%
“…Although there is no direct evidence in the literature regarding the effects of linaclotide on energy homeostasis, recent reports have indicated that the activation of its receptor Gucy2c is involved in the control of food intake [3] and EE [7] in rodents. Moreover, in humans circulating levels of proUGN are altered in obese adult subjects [8] and children [20]. The fact that oral linaclotide acts through the central nervous systems targeting BAT thermogenesis and EE without affecting feeding behavior is similar to our previous findings in which a central infusion of UGN was able to induce the same effects [7].…”
Section: Discussionsupporting
confidence: 86%
“…In PMV, GC‐C is mostly produced by neurons expressing anorexigenic leptin receptors (LepR), whereas in the VTA/SN, GC‐C is seen in neurons expressing tyrosine hydroxylase. After ingestion of food, prouroguanylin is secreted into the circulation, 62–64 and is processed into mature uroguanylin by hypothalamus 65 . This would result in activation of GC‐C and the increased accumulation of cGMP results in proopiomelanocortin and c‐Fos expression, which imparts the sense of satiety and reduces feeding 66 …”
Section: Extra‐intestinal Roles Of Gc‐cmentioning
confidence: 99%
“…One study reported a negative correlation between plasma fasting prouroguanylin concentration and BMI in girls, but a positive correlation in boys (40). Another study found female but not male adolescents with obesity had lower prouroguanylin concentrations (19).…”
Section: Discussionmentioning
confidence: 99%